2015
DOI: 10.1186/s40562-015-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Localized extensional tectonics in an overall reverse-faulting regime, Northeast Japan

Abstract: In Northeast Japan, it has been recognized that trench-normal compressional stresses, aligned in the approximate direction of plate convergence, tend to dominate stress fields over a broad region. However, a particularly notable event was the shallow, normal-faulting earthquake swarms with a T-axis oriented in the E-W or NW-SE directions that occurred immediately after the 2011 Tohoku-Oki earthquake near the Pacific coast in the Southeast Tohoku district. The stress tensor inversion represents the pre-Tohoku-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Over the past few years a similar behavior has been documented on different occasions: slip along the subduction interface triggered extensional earthquakes in the adjacent forearcs following both the 2010, Geophysical Research Letters 10.1002/2017GL076554 M w 8.8 Maule, Chile (Aron et al, 2013;Ryder et al, 2012) and the 2011, M w 9.0, Tohoku-Oki, Japan (Tsuji et al, 2013;Umeda, 2015) earthquakes. Similarly, slow slip events along the Calabrian subduction interface could trigger extensional earthquakes in its forearc.…”
Section: Geophysical Research Lettersmentioning
confidence: 52%
“…Over the past few years a similar behavior has been documented on different occasions: slip along the subduction interface triggered extensional earthquakes in the adjacent forearcs following both the 2010, Geophysical Research Letters 10.1002/2017GL076554 M w 8.8 Maule, Chile (Aron et al, 2013;Ryder et al, 2012) and the 2011, M w 9.0, Tohoku-Oki, Japan (Tsuji et al, 2013;Umeda, 2015) earthquakes. Similarly, slow slip events along the Calabrian subduction interface could trigger extensional earthquakes in its forearc.…”
Section: Geophysical Research Lettersmentioning
confidence: 52%
“…The Jhurio and Habbo anticlinal topographies (seen as high BG in Figure ) are more domal compared to the other asymmetrical anticlines. Umeda () reported a localized extensional tectonics in an overall reverse‐faulting regime in Northeast Japan that represents the pre‐Tohoku‐Oki earthquake stress field in the area as a normal‐faulting stress regime. Further, a study by Monaldi et al () in the inverted Salta group rift basin of the northwestern Argentina identified an east‐trending extensional structures including half gardens, rollover anticlines, and extensional fault‐propagation folds at its eastern border, which they interpreted as the preserved extensional structures.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, p revious studies have suggested that fluids exist in fault zone s in this region and affect the intense seismicity (Kato et al, 2013;Umeda et al, 2015;Yoshida et al, 2015;Zhao et al, 2015;Usuda et al, 2021). Yoshida (2021) examined the seismic waves in a fluid -driven earthquake swarm in Japan and suggested that the near-source (< a few kilometers) 𝑄 𝑠 -value was very small (< 50) during intense fluid migration.…”
Section: Discussionmentioning
confidence: 99%